DETERMINAN MINAT INDIVIDU DAN PENGARUHNYA TERHADAP PERILAKU PENGGUNAAN SISTEM INFORMASI BERBASIS TEKNOLOGI - Ruslinda Agustina (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2015)
This study aims to examine the determinants of behavioral of individualinterest to use technology-based information systems. This research is thedevelopment of models Theory of Reasoned Action (TRA) by Ozer and Yilmaz(2010), Lee et al. (2005), and Karami (2006). This study examined the influence ofperceived usefulness on individual interests, attitudes toward the interests ofindividual behavior, subjective norm against individual interests, perceivedbehavioral control towards individual interests, and the interests of theindividual against the behavior of the use of technology based informationsystems. The results of this research is demonstrated that perceived usefulness(KP), attitude toward the behavior (STP), subjective norm (NS), and perceivedbehavioral control (KPP), has positive effects on individual interest (MI), andindividual interest (MI) has positive effects on behavior (P) technology-basedinformation systems users.